Geopolitical Conflict and Indonesia’s Economic Stability - Melzatia, Shinta; Mahroji; Apollo; Zahri, Adli (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study analyses the role of the maqasid sharia in guiding the digitalisation of the Islamic economy to strengthen justice, sustainability, and the economic resilience of the ummah, while linking it to the Astagatra framework as the foundation of national resilience. Study Design/Methodology/Approach: This study uses a descriptive qualitative method with content analysis of the latest academic literature on digitalisation, Islamic economics, maqasid sharia, and national resilience. The study is guided by the TSR as a normative foundation and the Dynamic Capability Theory as an adaptive foundation. Findings: The findings indicate that fiscal discipline, export market diversification, and strengthening foreign exchange reserves are key strategies for mitigating external pressures. In addition, strict fiscal oversight and enforcement of public governance is crucial in preventing the erosion of the economic structure due to potential corruption. The theoretical implications of this study enrich the perspective of Prospect Theory by emphasising how risk perception and government decision-making shape the direction of macroeconomic policy. From a practical perspective, the findings provide a reference for policymakers to formulate anticipatory strategies against geopolitical shocks. The policy implications underscore the importance of striking a balance between short-term stability and sustainable development. Originality/Value: This study presents an integrative framework between the maqasid sharia, TSR, dynamic capabilities, and Astagatra, which is still rarely explored. Practical contributions lie in emphasising the measurement of sustainable use and accountable governance so that digitalisation supports community economic resilience and equitable national development.